1992
DOI: 10.1093/carcin/13.7.1261
|View full text |Cite
|
Sign up to set email alerts
|

Chemoprevention of mammary carcinogenesis by hydroxylated derivatives of d-limonene

Abstract: The monoterpene d-limonene has been shown to an effective, non-toxic chemopreventive agent in mammary and other rodent tumor models. The studies reported here investigated structure-activity relationships among limonene and three hydroxylated derivatives in the prevention of dimethylbenz[a]anthracene (DMBA)-induced mammary cancer. Rats were fed control or 1% limonene, carveol, uroterpenol or sobrerol diets from 2 weeks before to one week after carcinogen administration. Carveol, uroterpenol and sobrerol signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
60
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(63 citation statements)
references
References 0 publications
1
60
0
1
Order By: Relevance
“…The former prevent carcinogenic chemicals from interacting with target molecules, whereas the latter prevent the development and/or expression of the transformed cells. With respect to the mammary gland, agents such as retinoic acid (Welsch 1987, selenium (Ip & Medina 1987, and D-limonene (Crowell et al 1992) act as both blocking and suppressing agents, depending on the time intervals of application. It is more difficult to classify endogenous natural factors such as estrogen and progesterone.…”
Section: Protective Effect Of Pregnancymentioning
confidence: 99%
“…The former prevent carcinogenic chemicals from interacting with target molecules, whereas the latter prevent the development and/or expression of the transformed cells. With respect to the mammary gland, agents such as retinoic acid (Welsch 1987, selenium (Ip & Medina 1987, and D-limonene (Crowell et al 1992) act as both blocking and suppressing agents, depending on the time intervals of application. It is more difficult to classify endogenous natural factors such as estrogen and progesterone.…”
Section: Protective Effect Of Pregnancymentioning
confidence: 99%
“…The monocyclic monoterpene (ϩ)-and (Ϫ)-limonene enantiomers have been shown to be present in orange peel and other plants and are used as fragrances in household products and components of artificial essential oils (Crowell and Gould, 1994). The (ϩ)-limonene isomeric form is more abundantly present in these plants than the racemic mixture and (Ϫ)-isomeric form (Haudenschild et al, 2000).…”
mentioning
confidence: 99%
“…The (ϩ)-limonene isomeric form is more abundantly present in these plants than the racemic mixture and (Ϫ)-isomeric form (Haudenschild et al, 2000). It has previously been shown that (ϩ)-limonene has chemopreventive activities in experimental animal models including rats and mice (Crowell and Gould, 1994;el-Bayoumy, 1994). Some of the hydroxylated metabolites of (ϩ)-limonene, such as sobrerol, carveol, and uroterpenol, have been reported to be more potent than the parent compound in preventing mammary tumors caused by 7,12-dimethyldibenz [a]anthracene (Crowell et al, 1992).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Investigations of the in vivo disposition of d-limonene and its metabolites are limited. In rodents, radiolabeled d-limonene and/or its derived metabolites preferentially distribute to anatomical sites rich in fatty tissue such as adipose and mammary tissue rather than remaining in plasma [7]. Accurate assessment of the tissue distribution of d-limonene is a critical step to evaluate the potential of d-limonene as a chemopreventive agent in humans.…”
Section: Introductionmentioning
confidence: 99%